Hubungan Tindakan Perataan Laba dengan Reaksi Pasar atas Pengumuman Informas Laba Perusahaan yang Terdaftar di Bursa Efek Jakarta - Prihat Assih, M. Gundono (IAIKAP, 2000)
The investor's attention on net income numbers without regard to the oricedures used to genare them, has encourage manaegement to carry out earnings management. Include within earnings management is income smoothing. Income smoothing can be viewed in term of the redictopm om earmomgs varoability over a numbers of periods, or within a single period, as the movement toward unexpected level of reported earning. Objective of this study to examine the market reaction on earnings announcement due to the income smoothing. This study examine ninety nine companies which as cumulatiove abnormal retur five days surrounding the companies' earnings announcemnt date. Overall, the result of this study indicate that there is significant market raction surrouning the companies' earnings announcement date and these market reaction significantly difference between smoother companies and non-smoother companies. This study is hopes to give contributtion to the literature, that income smoothing practice can regard as a signal to better prediction of future earnings by investors and mean to decrease market raction on companies' earnings anouncement.